A138: Clinical Decision Support to Improve Preventive Care in Pediatric Systemic Lupus Erythematosus. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Nelson, Brittany
Abstract : Background/Purpose: Quality indicators, such as infection and cardiovascular disease (CVD) preventive care, for patients with systemic lupus erythematosus (SLE) have recently been published and can be utilized for assessing quality of care. Implementation of tools such as clinical decision support (CDS) within the electronic health record (EHR) can be utilized in quality care improvement efforts. The purpose of this quality improvement study is to test the chronic care model to study the relationship between CDS and rates of compliance with infection and CVD preventive care quality indicators for pediatric SLE patients at an outpatient rheumatology clinic. Methods: The study is a pilot retrospective design with a convenience sample. Documentation in the EHR of up to date vaccinations and lipid screen was measured before and after implementation of an electronic documentation template. Data for the comparative hypothesis was analyzed using Chi‐square test. Results: Baseline data was collected from 48 (70%) patient charts and post‐CDS data were collected from 20 (30%) patient charts. Before intervention, 15 (31.3%) patients received pneumonia vaccine and 17 (81.0%) of patients received vaccine after intervention. Sixteen (33.3%) patients received influenza vaccine before intervention and 20 (95.2%) received vaccine after intervention. Before intervention, 12 (25.0%) patients received lipid panels and 16 (76.2%) patients received lipid panels after intervention. All three differences were significantly different (Fisher's Exact p < 0.001). Patents were 9 times more likely to receive the pneumococcal vaccination and lipid panels and 40 times more likely to receive the influenza vaccination post intervention than before intervention.1 Conclusion: Use of EHR CDS was associated with improved rates of preventive care for pSLE patients in the Pediatric Rheumatology outpatient setting. Our results suggested that patients were more likely to receive a screening lipid panel, influenza vaccination and pneumococcal vaccination if the health care provider used the EHR template with CDS.